Features of application of the sampling theorem when processing narrow-band radio signals with known center frequency of the spectrum - Рогожкин, Е.В.; Подъячий, Ю.И.; Емельянов, Л.Я. (Radiotekhnika, 2020)
An option is presented for sampling narrow-band radio signals with a known center frequency of the spectrum, which can significantly reduce the amount of computational operations when processing such signals without significant loss of information about their parameters. In this case, narrowband is determined by the ratio of the spectrum width of the received radar signal and the operating frequency of the intermediate frequency amplifier, from the output of which the signal is fed to an analog-to-digital converter (ADC). A study of the proposed method of discretization is carried out, in which the repetition rate of the ADC interrogation pulses is determined by the frequency of the reference signal of the master system of a coherent radar and is selected multiple times lower than the operating frequency of the intermediate frequency amplifier. The synchronization of the ADC interrogation pulses is organized in such a way that any two adjacent samples are quadrature connected. This procedure allows you to determine the amplitude and phase of the received signal corresponding to each sample. This creates the conditions for determining the Doppler shift and envelope parameters of the signal. The results of calculating the relative error in determining the amplitude of the signal, which appears as a result of a mismatch in the frequency of the received signal with the frequency of the reference signal, are presented. For real cases, it does not exceed 1% and depends on the radar characteristics (sounding wavelength, multiplicity between the value of the intermediate frequency at which the processing is carried out, and the value of the sampling frequency), as well as on the magnitude of the object radial velocity and the initial phase difference between the output signal of the intermediate frequency amplifier and the reference signal. It is shown that this approach to converting the signal into a digital format is also applicable to signals with phase (0, π) manipulation if the duration of the code elements is significantly longer than the period of the reference signal.